Biogeography of Alaska paper birch (Betula neoalaskana): latitudinal patterns in chemical defense and plant architecture. Issue 2 (7th March 2016) - Stevens, Michael T.; Brown, Sarah C.; Bothwell, Helen M.; Bryant, John P.
Abstract: The latitudinal herbivory‐defense hypothesis (LHDH) predicts that plants near the equator will be more heavily defended against herbivores than are plants at higher latitudes. Although this idea is widely found in the literature, recent studies have called this biogeographic pattern into question. We sought to evaluate the LHDH in a high‐latitude terrestrial ecosystem where fire and mammalian herbivores may contribute to selection for higher levels of defensive chemistry. To address this objective, we collected seeds of Alaska paper birch ( Betula neoalaskana ) from nine locations along two north–south transects between 55° N and 62° N latitudes in western, interior Canada. The birch seeds were planted in pots in a common garden in Madison, Wisconsin, USA. From the resulting seedlings, we determined levels of chemical defense by assessing the density of resin glands, which have been shown to be negatively correlated with browsing. To assess plant architectural traits such as height, mean individual leaf area, and root‐to‐shoot ratio, we harvested a subset of the birch seedlings. Further, we used these traits to examine growth–defense trade‐offs. Contrary to the LHDH, we found a positive correlation between chemical defense and latitude. Investigating relationships with fire, we found a strong positive correlation between resin gland density and percentage of area annually burned (PAAB) around each collection location and also between PAAB and latitude. Additionally, birch seedlings originating from higher latitudes were shorter, smaller‐leaved, and rootier than their lower‐latitude counterparts. Growth–defense trade‐offs were observed in negative correlations between resin gland density and height and leaf size. Seedlings with higher resin gland densities also allocated less biomass to shoots and more to roots. These results further call into question the LHDH and provide specific information about latitudinal trends in plant defense at high, northern latitudes where fire is a major ecosystem driver and mammals are the main herbivores of deciduous trees such as birches. We propose that these interconnected relationships are the key drivers of the positive correlation between defense and latitude in B. neoalaskana . Understanding patterns of boreal plant defense and growth is especially important because high latitude ecosystems are particularly susceptible to climate change.